ANALYSIS OF IMPOLITENESS COMMENTS OF NETIZEN ON NAJWA SHIHAB YOUTUBE CHANNEL - Sinaga, Askima Rohmauli; Saragi, Christina Natalina; Silitonga, Harpen (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study is entitled